The Effect of Competence and Work Experience on Career Development Through Work Achievement as an Intervening Variable - Santika Novelya; Ina Karuehni (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – This study aims to determine the effect of competence, and work experience on career development through work achievement as an intervening variable at the Central Kalimantan Province labor and transmigration office.Design/Methodology/Approach – The data used in this study are primary data obtained from questionnaires. The sample size was 55 respondents who were employees of the Central Kalimantan Province labor and transmigration office. The type of research used is a quantitative approach. The research instrument used in this study used the Likert scale method. The analysis technique used is SMART PLS 3.0 data analysis technique.Findings - Based on the results of data analysis, it is obtained that competence has a significant effect on work performance, work experience has a significant effect on career development, and work performance has a significant effect on career development. As well as competence has no significant effect on career development and work experience has no significant effect on job performance